SARS-CoV2 Infection and the Importance of Potassium Balance - Causton, Helen C. (Frontiers in Medicine, 2021)
SARS-CoV2 infection results in a range of symptoms from mild pneumonia to cardiac arrhythmias, hyperactivation of the immune response, systemic organ failure and death. However, the mechanism of action has been hard to establish. Analysis of symptoms associated with COVID-19, the activity of repurposed drugs associated with lower death rates or antiviral activity in vitro and a small number of studies describing interventions, point to the importance of electrolyte, and particularly potassium, homeostasis at both the cellular and systemic level. Elevated urinary loss of potassium is associated with disease severity, and the response to electrolyte replenishment correlates with progression towards recovery. These findings suggest possible diagnostic opportunities and therapeutic interventions. They provide insights into comorbidities and mechanisms associated with infection by SARS-CoV2 and other RNA viruses that target the ACE2 receptor, and/or activate cytokine-mediated immune responses in a potassium-dependent manner.